Mitochondrial dysfunction is a hallmark of woody breast myopathy in broiler chickens - Greene, Elizabeth S.; Chen, Paula R.; Walk, Carrie; Bedford, Mike; Dridi, Sami (Frontiers in Physiology, 2025)
The woody breast (WB) myopathy poses significant economic and welfare concerns to the poultry industry, however, there is no effective strategy to mitigate this pathology due to its unknown etiology. After showing previously that hypoxia is a key factor in WB progression, we used here various techniques demonstrating dysregulated mitochondria (morphology, biogenesis, tethering, function, and bioenergetics) in WB-affected muscles and in hypoxic myoblasts compared to healthy tissues and normoxic cells, respectively. The increased levels of calcium (Ca2+) in both WB-affected tissues and hypoxic myoblasts suggested that mitochondrial Ca2+ overload is likely a leading cause for mitochondrial dysfunction that merits further in-depth investigation. These findings are the first, to the best of our knowledge, to provide fundamental insights into the underlying molecular mechanisms of WB and open new vistas for understanding the interplay between calcium, mitochondrial (dys)function, and avian muscle health for subsequent development of effective preventative/corrective strategies.